Global Health Security: Addressing Social Determinants of Health through programmes and other initiatives - Sivan Yegnanarayana Iyer Saraswathy (Taylor & Francis Group, 2021)
Introduction: Addressing social determinants of health (SDH) from a global health security perspective is important especially in low and middle income countries. Socioeconomic status, cultural, political and behavioural factors influence health and disease of the people. This paper seeks to describe how government programmes and other initiatives are expected to play an important role in addressing SDH and thereby improving health of the people. The analysis addresses both health and social policy issues. Context and Aim: The study assumes importance in view of India moving towards strengthening health and social security of its people through several policy-driven initiatives. Methods: This analysis classifies the 100 plus programmes launched by the Government of India into health, education, nutrition, social security, etc., and compares available indicators (2000-2018) Findings: The initiatives of the Government of India are expected to improve health and social security of its people, with focus on addressing health as well as social inequity. One of the programmes (Swachh Bharat Mission - clean India mission) has helped in avoiding 300,000 child deaths. Official survey results are not available for all indicators. Innovative contribution to policy, practice and/or research: Analysis of Government of India's policy-driven programmes and other initiatives with focus on livelihood improvement indicate that they are contributing to ensure health and social security; and are worth replicating in similar settings.